In vitro and in vivo activity analysis of poplar CLE dodecapeptides that are most divergent from Arabidopsis counterparts. (April 2021) - Song, Yawen; Yang, Shaohui; Wang, Jiehua
Highlights: Eight poplar CLE dodecapeptides were selected based on their lowest sequence similarity with Arabidopsis CLE peptides. With some poplar CLE peptides showing Arabidopsis-like activities, the others revealed different, opposite or novel activities. Both functional conservation and evolved unique activities exist for CLE peptides of land plants. Abstract: Intercellular communication mediated by the plant-specific CLAVATA3/ENDOSPERM SURROUNDING REGION (ESR)-related (CLE) family members is one of the fundamental mechanisms coordinating the development of complex bodies of plants. In this work, we chose 8 out of 38 putative CLE dodecapeptides encoded in the genome of P. trichocarpa based on their lowest sequence similarity with Arabidopsis CLE peptides, and investigated how such sequence variations affect their functional characteristics. In group 1, PtCLE16p faithfully retained the AtCLE1-7p activity, while PtCLE49p reversed the root-enhancing effect to an inhibitory one with two extra amino acid substitutions, which might have disrupted the capacity of PtCLE49p to recognize the corresponding receptors. In group 2, PtCLE9p conferred Arabidopsis with retarded root growth and suppressed phloem differentiation in a negative dominant manner just like AtCLE25 G6T did. PtCLE9p enhanced the vegetative growth in both basal and aerial rosettes by regulating the expression of AERIAL ROSETTE 1 ( ART1 ) and FRIGIDA ( FRI ) as well as the downstream FLOWERING LOCUS C ( FLC ) genes. In group 3, PtCLE34p and PtCLE5p slightly promoted primary root growth, while PtCLE40p revealed CLV3p-like and TDIF activity in root and hypocotyls, respectively. The remaining PtCLE18p in group 4 dramatically disturbed the expression of WOX5 and promoted the development of root hairs by repressing the expression of GLABRA2 ( GL2 ) gene, which encoded a negative regulator of epidermal cells differentiation towards root hairs. In summary, our data indicated that with significant functional conservation and common signaling machinery existing for CLE families of land plants, unique and diverse activities of CLE peptides have evolved to perform specific functions in different plant species.